2014
DOI: 10.1371/journal.pone.0088094
|View full text |Cite
|
Sign up to set email alerts
|

Burkholderia ambifaria and B. caribensis Promote Growth and Increase Yield in Grain Amaranth (Amaranthus cruentus and A. hypochondriacus) by Improving Plant Nitrogen Uptake

Abstract: Grain amaranth is an emerging crop that produces seeds having high quality protein with balanced amino-acid content. However, production is restricted by agronomic limitations that result in yields that are lower than those normally produced by cereals. In this work, the use of five different rhizobacteria were explored as a strategy to promote growth and yields in Amaranthus hypochondriacus cv. Nutrisol and A. cruentus cv. Candil, two commercially important grain amaranth cultivars. The plants were grown in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
36
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 79 publications
4
36
0
1
Order By: Relevance
“…Parra‐Cota et al . (), testing Burkholderia ambifaria and B. caribensis strains found that they are able to promote growth and yield of inoculated Amaranth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parra‐Cota et al . (), testing Burkholderia ambifaria and B. caribensis strains found that they are able to promote growth and yield of inoculated Amaranth.…”
Section: Discussionmentioning
confidence: 99%
“…Jiang et al (2012) found that inoculation of V. paradoxus in Pisum sativum promoted an increase in the biomass of roots and seedlings. Parra-Cota et al (2014), testing Burkholderia ambifaria and B. caribensis strains found that they are able to promote growth and yield of inoculated Amaranth.…”
Section: Discussionmentioning
confidence: 99%
“…Burkholderia genus abundantly proliferates in a broad range of ecological niches and wellknown plant-associated bacteria. Several species of Burkholderia were reported as PGPR in different plants viz., tomato [7], amaranthus [8], maize [9], rice [10], and sugarcane [11]. PGPR promote sugarcane growth through different mechanisms such as nitrogen fixation, production of plant hormone, antibiotic production, etc.…”
mentioning
confidence: 99%
“…5). The protein of T1 could be higher because it does not contribute to the available nitrogen despite of the organic fertilizer supply; the population of diazotrophic bacterium existing in this kind of fertilizer influences its availability in the plant (Parra-Cota et al, 2014). Additionally, a balance in elements like phosphorus, magnesium and other microelements contribute to the synthesis of protein (Marschner, 2012).…”
Section: Production and Composition Of The Grainmentioning
confidence: 99%